Caregiver Contribution to Self-Care of Chronic Illness Inventory: Evaluation of Measurement Properties in a Middle-Income Country - Sajmira Adëraj; Alta Arapi; Rocco Mazzotta; Alessandro Stievano; Dasilva Taci; Dhurata Ivziku; Vicente Bernalte-Martí; Ercole Vellone; Gennaro Rocco; Maddalena De Maria (Nursing Reports)
Background/Objectives: Caregivers engage in essential tasks that support patients’ well-being and survival, including administering medications, promoting healthy lifestyle choices, and monitoring and managing symptoms. To date, no valid and reliable instrument is available to assess Caregiver Contribution (CC) to self-care in chronic conditions in middle-income countries such as Albania. Aim: To evaluate the measurement properties (structural and construct validity, internal consistency reliability, stability, and measurement error) of the instrument CC to Self-Care of the Chronic Illness Inventory (CC-SC-CII) in Albanian caregivers caring for elderly people affected by multiple chronic conditions. Methods: A cross-sectional study. We enrolled caregivers of patients with multiple chronic conditions, from August 2020 to April 2021, if they were (a) 18 years of age or older and (b) were identified by the patient as the main unpaid caregiver. Results: Confirmatory factor analysis confirmed the two-factor structure of the CC to Self-Care Maintenance and Management scales and the one-factor structure of the CC to Self-Care Monitoring scale. Reliability estimates were adequate for all (coefficients ranging between 0.827 and 0.961). The construct’s validity was supported. The measurement error was adequate. Conclusions: The Albanian version of the CC to Self-Care of the Chronic Illness Inventory features sound measurement properties and is a valid and reliable instrument for assessing caregiver contribution to patient self-care behaviors in the Albanian population.